Developmental gene expression differences between humans and mammalian models - Cardoso-Moreira, Margarida; Sarropoulos, Ioannis; Velten, Britta; Mort, Matthew; Cooper, David N.; Huber, Wolfgang; Kaessmann, Henrik (Cell reports, 2020)
Identifying the molecular programs underlying human organ development and how they differ from model species is key for understanding human health and disease. Developmental gene expression profiles provide a window into the genes underlying organ development and a direct means to compare them across species. We use a transcriptomic resource covering the development of seven organs to characterize the temporal profiles of human genes associated with distinct disease classes and to determine, for each human gene, the similarity of its spatiotemporal expression with its orthologs in rhesus macaque, mouse, rat, and rabbit. We find clear associations between spatiotemporal profiles and the phenotypic manifestations of diseases. We also find that half of human genes differ from their mouse orthologs in their temporal trajectories in at least one of the organs. These include more than 200 genes associated with brain, heart, and liver disease for which mouse models should undergo extra scrutiny.
Gesehen am 27.11.2020